Peran Manajemen Dyandra Convention Center dalam Pengembangan Industri MICE di Surabaya - Alan Sinta, Selly; Bambang, Suharto (Politeknik Pariwisata NHI Bandung, 2025)
This study aims to explore the role of the management of Dyandra Convention Center (DCC) in the development of the MICE (Meetings, Incentives, Conferences, and Exhibitions) industry in Surabaya. Using a qualitative approach and case study method, this research analyzes four key aspects: managerial strategies, marketing effectiveness, local economic contributions, and social impacts on the surrounding community. The findings show that DCC plays a significant role in strengthening Surabaya's branding as a MICE hub, with managerial strategies focusing on operational efficiency and service innovation. In terms of marketing, DCC has successfully increased Surabaya’s appeal through the use of digital marketing and collaboration with stakeholders. Additionally, DCC contributes significantly to the local economy, particularly through the development of supporting sectors such as hospitality and SMEs. The social impact of DCC is also evident through the empowerment of the local community in various MICE activities. This study recommends further development in digitalization and destination policies to support the sustainability of the MICE industry in Surabaya.